Bank Digital Indonesia: Influence Anlysis Financial Ratio - Zahrani, Syifa Aulia; Hakim, Dinda Aulia; Widayanti, Asti; Fahrudin, Tora (Universitas Pamulang, 2023)
Abstract As a result of the impact of digital technology development, traditional banks are giving way to digital banks in the banking industry. The operational and profitability financial ratios, which both have a partial and simultaneous impact, can be used to determine how well the banking industry is performing. This study sets out to quantify the impact of operational ratio on Bank Digital's profitability. The operating ratios used in this study to assess bank performance are operating income (BOPO), non-performing financing (NPF), financing to deposits (FDR), and profitability (ROE), with profitability (ROE) as the independent variable. The data for this quantitative study came from the annual reports of six of the seven digital banks that were originally established with OJK for the period of 2017 to 2022. Descriptive statistics are used in the data processing, and linear regression is used in the data analysis, partially together with the coefficient of determination test, t test, and simultaneous analysis with hypothesis testing, or f test. According to the findings of the study's hypothesis testing, the NPF value has no bearing on the profitability ratio value, however the FDR and BOPO values have an impact on profitability. The simultaneous testing of these three factors reveals that BOPO, NPF, and FDR also have an impact on profitability. Abstrak Akibat dampak perkembangan teknologi digital, bank tradisional mulai tergeser oleh bank digital dalam industri perbankan. Rasio keuangan operasional dan profitabilitas, yang mempunyai dampak parsial dan simultan, dapat digunakan untuk mengetahui seberapa baik kinerja industri perbankan. Penelitian ini bertujuan untuk mengukur dampak rasio operasional terhadap profitabilitas Bank Digital. Rasio operasional yang digunakan dalam penelitian ini untuk menilai kinerja bank adalah pendapatan operasional (BOPO), non-performing financing (NPF), financing to deposit (FDR), dan profitabilitas (ROE), dengan profitabilitas (ROE) sebagai variabel independen. Data penelitian kuantitatif ini berasal dari laporan tahunan enam dari tujuh bank digital yang semula didirikan bersama OJK periode 2017 hingga 2022. Statistik deskriptif digunakan dalam pengolahan data, dan regresi linier digunakan dalam analisis data. , secara parsial dilakukan uji koefisien determinasi, uji t, dan analisis simultan dengan uji hipotesis atau uji f. Berdasarkan temuan pengujian hipotesis penelitian, nilai NPF tidak mempunyai pengaruh terhadap nilai rasio profitabilitas, namun nilai FDR dan BOPO mempunyai pengaruh terhadap profitabilitas. Pengujian ketiga faktor tersebut secara simultan menunjukkan bahwa BOPO, NPF, dan FDR juga mempunyai pengaruh terhadap profitabilitas.